Gender, age, and education: do they really moderate online music acceptance? - Norazah Mohd Suki (IBIMA Publishing, 2011)
The objective of this paper is to investigate whether gender, age, and education really moderate online music acceptance of early adopters. An empirical survey was used to test the hypotheses. Data were collected from a total of 200 questionnaires distributed to early adopters of online music and were analysed using Structural Equation Modeling (SEM) via the Analysis of Moment Structure (AMOS 16) computer program. Results enumerates that younger people (younger than 25 years), male and higher educated were more strongly affected by Perceived Playfulness and Perceived Ease of Use towards online music. This study helps practitioners to extend online music market with greater understanding about early adopters’ willingness to involve in online music purchase. The paper rounds off with conclusions and an agenda for future research in this area.